Os efeitos da mudança de regime previdenciário nas dívidas dos municípios cearenses - Silva Júnior, Francisco Ferreira da (2018)
In the decade of two thousand, several municipalities of Ceará, began to adopt their own Social Security Regimes, replacing National Institute of Social Security (INSS) for their employees. On the one hand, private pension schemes can serve as temporary “banks” for city councils, which can circumstantially increase their social security debts without having their transfers blocked by debts with the INSS. On the other hand, the regimes themselves may have more attractive and cheaper rates, allowing councils for better adjustment of accounts. The present study seeks to analyze the net balance of these possible effects using a panel econometric model with municipal information on budgets for the period from 2004 to 2011. The results show that the change in regime has led to an increase in social security and supplier debts, thus giving rise to the idea that regime change is another factor of pressure in the municipal treasury.